1964
DOI: 10.1901/jeab.1964.7-309
|View full text |Cite
|
Sign up to set email alerts
|

REACTION TIME AS A FUNCTION OF STIMULUS INTENSITY FOR THE MONKEY1

Abstract: Monkeys were trained to release a telegraph key in response to a visual or auditory stimulus. The latency of the key release response was measured for different stimulus intensities. In general, the relation between latency and intensity is inverse and exponential with greater variability of latency at the lower intensities. Some preliminary data involving differential reinforcement of short latencies are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…For levels near the hearing threshold, statistical measures of RT are affected by the animal's response criterion (Heil et al, 2006) and relatively long RTs often occur that result in deviation from simple power law behaviour (Pins and Bonnet, 2000;Stebbins and Miller, 1964;Wagner et al, 2004). Therefore, one or two median RTs (depending on the frequency) to low intensity signals (SnL <30 dB) were omitted when this substantially improved the model fits (omitted data are shown in Fig.…”
Section: Analysis Of the Reaction Timesmentioning
confidence: 99%
“…For levels near the hearing threshold, statistical measures of RT are affected by the animal's response criterion (Heil et al, 2006) and relatively long RTs often occur that result in deviation from simple power law behaviour (Pins and Bonnet, 2000;Stebbins and Miller, 1964;Wagner et al, 2004). Therefore, one or two median RTs (depending on the frequency) to low intensity signals (SnL <30 dB) were omitted when this substantially improved the model fits (omitted data are shown in Fig.…”
Section: Analysis Of the Reaction Timesmentioning
confidence: 99%
“…The approach was first applied to non-human primates in studies by Stebbins and colleagues (Miller et al 1969;Stebbins and Miller 1964), who characterized the relationship between RT and stimulus intensity (visual or auditory). These investigators reported equal latency contours that share many of the features of our present observations (Stebbins 1966), including a compressed range of latency/loudness measures at high frequencies (Fig.…”
Section: Previous Animal Psychophysical Studies Of Loudness Perceptionmentioning
confidence: 99%
“…There is evidence that Grice's theory can be applied to monkeys as well as humans. When Stebbins and Miller (1964) trained monkeys to press a key in response to tones of various intensities, they found that the intensity effect was greater when every response was rewarded than when only fast responses were rewarded. Finally, Henriksen (1971) attempted to manipulate his (human) subjects' response criterion by presenting either no feedback regarding their reaction time or feedback which was false but credible.…”
Section: Pure Strong Blocksmentioning
confidence: 99%